Prevalence of Teenage Pregnancy among Girls Aged 13 to 19 Years in Nyagatare District, Rwanda - Agnes, NAKATO; Amos, HABIMANA (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Teenage pregnancy remains a critical public health concern in sub-Saharan Africa, with profound implications for maternal and child health, educational attainment, and socioeconomic development. Nyagatare District in Rwanda has reported elevated rates of adolescent pregnancies compared to national averages; yet current prevalence data remain inadequately documented. A cross-sectional study was conducted among 427 adolescent girls aged 13–19 years in Nyagatare District between January and December 2024. Quantitative data were collected using structured questionnaires covering pregnancy history, age at first pregnancy, birth outcomes, pregnancy planning status, and antenatal care utilization. Data were analyzed using SPSS software with descriptive statistics including frequencies, percentages, and 95% confidence intervals to determine prevalence rates across different age groups and sociodemographic characteristics. The overall prevalence of teenage pregnancy was 13.1% (95% CI: 10.2–16.5%, n=56). Among those who had been pregnant, 55.4% (n=31) experienced their first pregnancy before age 16, while 44.6% (n=25) were 17 years or older. The vast majority of pregnancies were unplanned (91.1%, n=51), with only 8.9% (n=5) reporting planned pregnancies. Among pregnant adolescents, 67.9% (n=38) received antenatal care while 32.1% (n=18) did not access such services. Birth outcomes showed that 92.9% (n=52) had not yet given birth, while 7.1% (n=4) had delivered one child. The prevalence rate was substantially higher than the 7.3% national average reported in the 2020 Rwanda Demographic and Health Survey. Teenage pregnancy prevalence in Nyagatare District is substantially elevated compared to national averages, with the majority occurring before age 16 and characterized by unplanned pregnancies. These findings highlight an urgent need for targeted adolescent reproductive health interventions in the district to reduce early pregnancy rates and improve access to family planning and antenatal care services.